2019
DOI: 10.1080/19476337.2019.1569167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasound irradiation on the particle size distribution and rheological properties of red wine

Abstract: 2019) Effect of ultrasound irradiation on the particle size distribution and rheological properties of red wine, ABSTRACT In this paper, the effects of ultrasonic treatment on the particle size distribution and rheological properties of red wine were investigated to explore the insight changing mechanism of organoleptic attributes. The results indicate that ultrasound irradiation did affect the particle size distribution by increasing the intervals of particle size distribution, which, especially for the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…As shown in Figure 4(a)-(c), the rheological characteristics of red wine were indeed affected along with different microwave power, temperature, and time. According to the relationship between shear rate (γ) and shear stress (τ), fluids can be divided into Newtonian and non-Newtonian fluids [22,23]. According to the results of rheological curve, the shear rate, and shear stress of red wine in the untreated samples and the microwave-treated sample were not linear, which showed that red wine under different conditions was non-Newtonian fluids; and the shear stress of all red wine quickly increased with the increase of shear rate, which could indicate that microwave treatment couldn't change the fluid characteristics of red wine.…”
Section: Rheological Characteristics Of Untreated and Microwave-treat...mentioning
confidence: 99%
“…As shown in Figure 4(a)-(c), the rheological characteristics of red wine were indeed affected along with different microwave power, temperature, and time. According to the relationship between shear rate (γ) and shear stress (τ), fluids can be divided into Newtonian and non-Newtonian fluids [22,23]. According to the results of rheological curve, the shear rate, and shear stress of red wine in the untreated samples and the microwave-treated sample were not linear, which showed that red wine under different conditions was non-Newtonian fluids; and the shear stress of all red wine quickly increased with the increase of shear rate, which could indicate that microwave treatment couldn't change the fluid characteristics of red wine.…”
Section: Rheological Characteristics Of Untreated and Microwave-treat...mentioning
confidence: 99%
“…Xu et al. (2019) applied the US nonthermal processing technology to understand the mechanisms of the organoleptic qualities of Cabernet Sauvignon red wine by investigating if the particle sizes and rheology are affected by the treatment interaction. The red wine was irradiated in an ultrasonic bath at 120–300 W power, and the ratio of particles smaller than 1.000 μ$\umu $m declined from 92.80% to 90.50%.…”
Section: Physicochemical Biological and Sensory Effects Of Us On Alco...mentioning
confidence: 99%
“…Xu et al (2019) applied the US nonthermal processing technology to understand the mechanisms of the organoleptic qualities of Cabernet Sauvignon red wine by Selected international regulations in the wineries and alcoholic beverage industries concerned with ultrasound technology…”
mentioning
confidence: 99%
“…Consumers expect to find clarity or absence of turbidity in quality wines. Turbidity (or light scattering) in wine is due to the presence of particles in suspension that block light rays, thus diffusing some of the light in different directions and creating what is called the Tyndall effect (Xu et al, 2019). This makes the wine seem opaque to various degrees.…”
Section: Temperature and Wine Stabilitymentioning
confidence: 99%